Mechanical, Thermal and Morphological Properties of Poly(lactic acid)/Natural Rubber Nanocomposites - Mohd Bijarimi, Mat Piah; Sahrim, Ahmad; Rozaidi, Rasid (SAGE Publications, 2014)
This paper reports a melt blend of poly(lactic acid)/liquid natural rubber with Cloisite C30B (C30B). The mechanical, thermal and morphological properties of poly(lactic acid)/liquid natural rubber and nanocomposites were investigated. Results indicate that Young’s modulus and flexural modulus increased with the addition of C30B to the poly(lactic acid)/liquid natural rubber blend. The elongation at break of poly(lactic acid)/liquid natural rubber increased significantly as compared to nanocomposite with 1% of C30B, i.e. from 37.3% to 62.4%. Nevertheless, the elongation at break and impact strength decreased gradually when nanoclay content increased above 3%, suggesting the addition of clay changed the strain response in the blend systems. The incorporation of nanoclay in the poly(lactic acid)/liquid natural rubber blends lowered the glass transition temperature values relative to poly(lactic acid). This behavior may be associated with more free volume available in the nanocomposite blend systems compared with pure poly(lactic acid). Morphological analyses by scanning electron microscope and transmission electron microscope revealed that different types of morphologies exist for poly(lactic acid)/liquid natural rubber and nanocomposites. This study indicates that poly(lactic acid)/liquid natural rubber-toughened nanocomposites with a higher modulus and that thermal stability could be produced.